2003
DOI: 10.1093/intimm/dxg083
|View full text |Cite
|
Sign up to set email alerts
|

Bovine IgM antibodies with exceptionally long complementarity‐determining region 3 of the heavy chain share unique structural properties conferring restricted VH + Vλ pairings

Abstract: Naturally occurring antibody repertoires of cattle (Bos taurus) include a group of IgMlambda antibodies with exceptionally long complementarity-determining region 3 of the heavy chain (CDR3H) segments, containing multiple Cys residues. These massive CDR3H segments will greatly influence the tertiary and quaternary structures of the bovine IgM combining sites. As an antibody's combining site is formed by both heavy and light chains, we have analyzed the nucleotide sequences and structural properties of the lamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 40 publications
0
54
0
Order By: Relevance
“…Therefore, in many species, relatively few antibody precursors can be affinity-matured to HIV bnAbs. Cows, however, produce antibodies with HCDR3s that average ~26 amino acids in length with an ultralong subset (10–15% of the repertoire) that can be over 70 amino acids in length 46,8,9,16 . Previous work has shown that repeated immunization over multiple years with a non-well-ordered Env trimer in cows can lead to some neutralization breadth in the immunoglobulin-rich colostrum 1719 , although with relatively low potency.…”
Section: Main Textmentioning
confidence: 99%
“…Therefore, in many species, relatively few antibody precursors can be affinity-matured to HIV bnAbs. Cows, however, produce antibodies with HCDR3s that average ~26 amino acids in length with an ultralong subset (10–15% of the repertoire) that can be over 70 amino acids in length 46,8,9,16 . Previous work has shown that repeated immunization over multiple years with a non-well-ordered Env trimer in cows can lead to some neutralization breadth in the immunoglobulin-rich colostrum 1719 , although with relatively low potency.…”
Section: Main Textmentioning
confidence: 99%
“…The complementary determining regions (CDRs) of the heavy-and lightchain variable regions of an antibody interact with an antigen, and CDR3 is the most diverse (56,57). Unlike in mouse antibodies, the bovine Ig heavy chain has a very long CDR3, which can be more than 60 residues in length (58,59) and may span a spatial distance of up to 45 Å. As the CDR3 region is the most heterogenous, the three-dimensional structure of the antigen-binding site is influenced by its length (60).…”
Section: Figmentioning
confidence: 99%
“…The only known exception to this structural paradigm for antigen recognition is the variable lymphocyte receptor of jawless vertebrates, which use a leucine-rich repeat scaffold with variable loops to bind antigen (Alder et al, 2005; Pancer et al, 2004). Interestingly, some vertebrates, such as Bos taurus , have a very limited diversity of V gene segments (Berens et al, 1997; Lopez et al, 1998; Saini et al, 2003; Sinclair et al, 1997; Zhao et al, 2006), yet maintain a perfectly robust adaptive immune response, suggesting unique diversification mechanisms at work to generate a functional antibody repertoire.…”
Section: Introductionmentioning
confidence: 99%